(p)ppGpp Metabolism and Antimicrobial Resistance in Bacterial Pathogens - Das, Bhabatosh; Bhadra, Rupak K. (Frontiers in Microbiology, 2020)
Single cell microorganisms including pathogens relentlessly face myriads of physicochemical stresses in their living environment. In order to survive and multiply under such unfavorable conditions, microbes have evolved with complex genetic networks, which allow them to sense and respond against these stresses. Stringent response is one such adaptive mechanism where bacteria can survive under nutrient starvation and other related stresses. The effector molecules for the stringent response are guanosine-5’-triphosphate 3’-diphosphate (pppGpp) and guanosine-3’, 5’-bis(diphosphate) (ppGpp), together called (p)ppGpp. These effector molecules are now emerging as master regulators for several physiological processes of bacteria including virulence, persistence and antimicrobial resistance. (p)ppGpp may work independently or along with its cofactor DksA to modulate the activities of its prime target RNA polymerase and other metabolic enzymes, which are involved in different biosynthetic pathways. Enzymes involved in (p)ppGpp metabolisms are ubiquitously present in bacteria and categorized them into three classes, i.e., canonical (p)ppGpp synthetase (RelA), (p)ppGpp hydrolase/synthetase (SpoT/Rel/RSH) and small alarmone synthetases (SAS). While RelA gets activated in response to amino acid starvation, enzymes belonging to SpoT/Rel/RSH and SAS family can synthesize (p)ppGpp in response to glucose starvation and several other stress conditions. In this review, we will discuss about the current status of the following aspects: (i) diversity of (p)ppGpp biosynthetic enzymes among different bacterial species including enteropathogens, (ii) signals that modulate the activity of (p)ppGpp synthetase and hydrolase, (iii) effect of (p)ppGpp in the production of antibiotics and (iv) role of (p)ppGpp in the emergence of antibiotic resistant pathogens. Emphasis has been given to the cholera pathogen Vibrio cholerae due to its sophisticated and complex (p)ppGpp metabolic pathways, rapid mutational rate and acquisition of antimicrobial resistance determinants through horizontal gene transfer. Finally, we discuss the prospect of (p)ppGpp metabolic enzymes as potential targets for developing antibiotic adjuvants and tackling persistence of infections.